PENGARUH CITRA PERUSAHAAN, KUALITA PELAYANAN, LOKASI DAN HARGA TERHADAP MINAT BELI ULANGTABUNG GAS LPG 12 KG PADAPT.JALAHAN ARTA PRIMARANTAUPRAPAT - Ummi Batubara, Nur Syamsu; Nasution, Ade Parlaungan; Prayoga, Yudi (Universitas Labuhanbatu, 2021)
This study aims to determine the effect of company image, service quality, location and price on the repurchase interest of 12 KG LPG gas cylinders at PT. Jalah arta Prima Rantauprapat. The population in this study were consumers who made purchases of LPJ gas cylinders at PT. Jalah Arta Prima Rantauprapat, namely 541 people. The sample used in this study is to use the incidental sampling method (Incidental Sampling). Respondents in this study are consumers who purchase LPG gas cylinders at PT. Arta Prima Rantauprapat totaled 139 respondents. Analysis of the data obtained used quantitative and qualitative data analysis. Testing the feasibility of the research instrument and descriptive analysis of the characteristics of respondents using the softwareSPSS (Statistical Package for the Social Science) version 20.